2007
DOI: 10.1111/j.1365-2672.2006.03204.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of intestinal bacteria and their adhesive capability in relation to the intestinal mucus of carp

Abstract: Aims:  The aims of the present study are to characterize the intestinal microbial community displaying a high‐adhesive capability in fish, and to evaluate the relationship between mucosal adhesion of intestinal bacteria and fish health and disease. Methods and Results:  A total of 707 aerobic bacteria isolated from carp intestine that were maintained under either feeding (feeding group) or no‐feeding (no‐feeding group) conditions and were performed adhesive assay. Isolates were divided into three categories on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…The genus Aeromonas was significantly more abundant in the intestinal mucosa than in the intestinal content. These observations are consistent with previous studies reporting that Aeromonas with adhesive capability can colonise the surface of intestinal mucosa and that the intestine might be a primary location for stressinduced infections by Aeromonas [53]. However, bacteria associated with the mucosa may be regarded as indigenous species, and they are involved in host nutrition, mucosal defence and host immunity [54].…”
Section: −3supporting
confidence: 82%
“…The genus Aeromonas was significantly more abundant in the intestinal mucosa than in the intestinal content. These observations are consistent with previous studies reporting that Aeromonas with adhesive capability can colonise the surface of intestinal mucosa and that the intestine might be a primary location for stressinduced infections by Aeromonas [53]. However, bacteria associated with the mucosa may be regarded as indigenous species, and they are involved in host nutrition, mucosal defence and host immunity [54].…”
Section: −3supporting
confidence: 82%
“…Pathogens as Escherichia coli that inhabit the gastrointestinal tract of pigs present surface proteins that recognise in a specific manner receptors in the mucus (Fang et al, 2000). Moreover these results support the previously observed by Namba et al (2007) who reported that intestinal bacteria which colonise the surface of intestinal mucosa, showed a high-adhesive capability to fish intestinal mucus. Adhesive strains isolated from faeces could be released to the lumen during the renewal of mucus.…”
Section: Resultssupporting
confidence: 82%
“…The adhesive capability of intestinal bacteria is essential for colonization and growth in the intestinal tract (Namba et al, 2007). Hence, highly adhesive bacteria can reside for a longer period in intestinal tracts.…”
Section: Introductionmentioning
confidence: 99%